2013
DOI: 10.1007/s11116-013-9498-x
|View full text |Cite
|
Sign up to set email alerts
|

Economical welfare maximisation analysis: assessing the use of existing Park-and-Ride services

Abstract: This paper assesses travellers' responses to the use of existing Park-and-Ride (P&R) services based on an economical welfare maximisation approach. Specifically, the paper presents a modelling framework to estimate consumer surplus and producer surplus (business profits) on the basis of modal choice probabilities. The paper draws on evidence from Stated Preference surveys conducted around two P&R sites in Sapporo, Japan, where P&R services occupy a modest market space. Overall, the results suggest that busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, good publicity and positive information on park and ride use on different social media platforms significantly increased the tendency to use park and ride and improved the utility of the mode. Apart from parking fees at park and ride facilities ( 28 , 29 ), researchers also identified that increasing parking costs at the destination greatly influenced the decision to switch from car to park and ride ( 18 , 21 , 30 , 31 ). In other research, the effects of context variables, such as weather, carrying luggage, other passengers, travel purpose, and time of day, on the decision-making process of car drivers with regard to choosing park and ride were also studied ( 32 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, good publicity and positive information on park and ride use on different social media platforms significantly increased the tendency to use park and ride and improved the utility of the mode. Apart from parking fees at park and ride facilities ( 28 , 29 ), researchers also identified that increasing parking costs at the destination greatly influenced the decision to switch from car to park and ride ( 18 , 21 , 30 , 31 ). In other research, the effects of context variables, such as weather, carrying luggage, other passengers, travel purpose, and time of day, on the decision-making process of car drivers with regard to choosing park and ride were also studied ( 32 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on parking behavioral survey data, Clayton et al [29] stated that the size of the group of people traveling together also impacts travelers' choice behavior of P&R facilities. Based on scenarios with different modes of transportation, Kono et al [30] found that the cost of transportation trips and travel time have a significant impact on the choice of P&R facilities. Very recently, several studies have been conducted on the choice behavior of demanders in shared parking.…”
Section: Influencing Factors Of Parkingmentioning
confidence: 99%
“…In their research, the primary finding was that introduction of daily parking fees did not cause significant changes in access mode choice, facility location, or line-haul mode of park-and-ride users. 10 Kono et al 11 assess travelers' responses to the use of existing P&R services based on an economical welfare maximization approach, and they considered that P&R choice is not only influenced by parking fees but also by the fares and other attributes of alternative transportation modes.…”
Section: Introductionmentioning
confidence: 99%